2020
DOI: 10.1002/ecy.2988
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance legacies increase and synchronize nutrient concentrations and bacterial productivity in coastal ecosystems

Abstract: Long-term ecological research can resolve effects of disturbance on ecosystem dynamics by capturing the scale of disturbance and interactions with environmental changes. To quantify how disturbances interact with long-term directional changes (sea-level rise, freshwater restoration), we studied 17 yr of monthly dissolved organic carbon (DOC), total nitrogen (TN), and phosphorus (TP) concentrations and bacterioplankton productivity across freshwater-tomarine estuary gradients exposed to multiple disturbance eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 73 publications
1
17
0
Order By: Relevance
“…There is a critical need and a timely opportunity to coordinate experimental, observation, and modeling approaches to understand saltwater intrusion impacts in coastal wetlands that will inform effective policies and management. In order to better manage coastal ecosystems into the future, we need to understand how disturbance legacies interact with long-term environmental changes-such as sea-level rise and saltwater intrusion-to influence how ecosystems respond to long-term presses and short-term pulses of subsidies and stressors (Odum et al 1979, Odum et al 1995, Kominoski et al 2020.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a critical need and a timely opportunity to coordinate experimental, observation, and modeling approaches to understand saltwater intrusion impacts in coastal wetlands that will inform effective policies and management. In order to better manage coastal ecosystems into the future, we need to understand how disturbance legacies interact with long-term environmental changes-such as sea-level rise and saltwater intrusion-to influence how ecosystems respond to long-term presses and short-term pulses of subsidies and stressors (Odum et al 1979, Odum et al 1995, Kominoski et al 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Although ecosystems have some capacity to recover structure and function (Holling 1973), disturbances often elicit changes in ecosystem state (Scheffer et al 2001, Peters et al 2011, Grimm et al 2017. Therefore, legacies of disturbance interactions influence how ecosystems respond to long-term presses and short-term pulses of subsidies and stressors (Odum et al 1979, Odum et al 1995, Kominoski et al 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term monitoring data indicated that abrupt and sustained increases in TP and DOC from marine storm surges and severe low-temperature events increase bacterioplankton productivity for extended periods, and that these responses are more pronounced in SRS than in the TS/Ph transect [36]. Despite these striking differences in BP, the composition of the freshwater microbial communities was not significantly different between the two transects.…”
Section: Freshwater Marsh Communitiesmentioning
confidence: 99%
“…Disturbance responses are fundamentally important in most ecosystems, because they can affect population densities, nutrient pools and ecological processes, re-set ecosystems to new positions in their successional pathways, and even tip them into new states (Pickett and White 1985;Kominoski et al 2020). At the same time, the nature of disturbance responses can vary so much within and among ecological systems that a synthetic understanding has been difficult to obtain (Peters et al 2011;Gaiser et al 2020). This challenge has been exacerbated by inconsistent use of relevant terminology in different papers (Standish et al 2014;Angeler and Allen 2016).…”
mentioning
confidence: 99%
“…Despite a long history of research, a fundamental disconnect remains between conceptual treatments and empirical studies of disturbance responses. Conceptual models typically focus on the importance of ecosystem conditions and legacies of previous perturbations in mediating disturbance (Peters et al 2011;Grimm et al 2017;Gaiser et al 2020), but usually represent the ecosystem as a single variable, assuming that multiple response variables can somehow be combined into a single index of "ecosystem state" (Pimm 1984;Blonder et al 2014; Barros et al 2016), and rarely explicitly quantify disturbance magnitude or recovery (Seidl et al 2014). In contrast, empirical work has long recognized that perturbations affect multiple ecosystem variables differently, and thus that disturbance magnitude and recovery trajectories may differ among ecosystem components (Odum 1969;Turner 2010;Jentsch and White 2019;Schäfer et al 2019).…”
mentioning
confidence: 99%